2009
DOI: 10.1089/thy.2008.0342
|View full text |Cite
|
Sign up to set email alerts
|

A Birth Cohort Analysis of the Incidence of Papillary Thyroid Cancer in the United States, 1973–2004

Abstract: While a period effect that is likely due to advancements in diagnostic techniques and increased medical detection of small thyroid nodules may explain some of the observed increase in the incidence, we speculate that birth cohort-related changes in environmental exposures (such as increased exposure to diagnostic X-rays and polybrominated diphenyl ethers) have also contributed to the observed increase in papillary thyroid cancer during the past decades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
115
1
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(129 citation statements)
references
References 14 publications
7
115
1
6
Order By: Relevance
“…In our study, the thyroid cancers accounted for 1.1% of all cancers; this finding is consistent with the literature data where the prevalence is usually around 1% (Davies et al, 2006). The evolution of the incidence of thyroid cancers can vary within a country, due to the occurrence of a particular epidemiological context or a change in diagnostic performance (Cotterill et al, 2001;Zhu et al, 2009). In the first case, it's necessary to highlight the influence of nuclear radiation.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the thyroid cancers accounted for 1.1% of all cancers; this finding is consistent with the literature data where the prevalence is usually around 1% (Davies et al, 2006). The evolution of the incidence of thyroid cancers can vary within a country, due to the occurrence of a particular epidemiological context or a change in diagnostic performance (Cotterill et al, 2001;Zhu et al, 2009). In the first case, it's necessary to highlight the influence of nuclear radiation.…”
Section: Discussionsupporting
confidence: 91%
“…A recent ecologic study using the Surveillance, Epidemiology and End Results (SEER) data indicated that higher levels of healthcare access are associated with higher papillary thyroid cancer rates, which provided supportive evidence for the overdiagnosis of thyroid cancer (3). However, other studies offered divergent opinions (4,5). The study based on the Department of Defense's Automated Central Tumor Registry found that the age-adjusted incidence rate of thyroid cancer in the military was significantly higher than the general population, and the rates varied by military service branch, suggesting that heightened medical surveillance does not appear to explain the temporal increase in thyroid cancer incidence fully (4).…”
Section: Introductionmentioning
confidence: 99%
“…A number of factors are taken into consideration for the geographical and biographical differences in the different stages. In addition to genetic factors [14], nutritional reasons, among others, play a role [15]. In this context, there is an association of FTC with a lack of dietary iodine [15].…”
mentioning
confidence: 99%
“…In addition to genetic factors [14], nutritional reasons, among others, play a role [15]. In this context, there is an association of FTC with a lack of dietary iodine [15]. In a recently published study of 4955 patients and 7348 assessed thyroid nodules, it was shown that there is not a linear association of increasing nodule size and malignancy risk [16].…”
mentioning
confidence: 99%